Genomic study of Acinetobacter baumannii strains co-harboring blaOXA-58 and blaNDM-1 reveals a large multidrug-resistant plasmid encoding these carbapenemases in Brazil - Rodrigues, Daiana Cristina Silva; Silveira, Melise Chaves; Pribul, Bruno Rocha; Karam, Bruna Ribeiro Sued; Picão, Renata Cristina; Kraychete, Gabriela Bergiante; Pereira, Felicidade Mota; de Lima, Rildo Mendes; de Souza, Antonio Kleber Gomes; Leão, Robson Souza; Marques, Elizabeth Andrade; Rocha-de-Souza, Cláudio Marcos; et al. (Frontiers in Microbiology, 2024)
Acinetobacter baumannii contributes significantly to the global issue of multidrug-resistant (MDR) nosocomial infections. Often, these strains demonstrate resistance to carbapenems (MDR-CRAB), the first-line treatment for infections instigated by MDR A. baumannii. Our study focused on the antimicrobial susceptibility and genomic sequences related to plasmids from 12 clinical isolates of A. baumannii that carry both the blaOXA-58 and blaNDM-1 carbapenemase genes. Whole-genome sequencing with long-read technology was employed for the characterization of an A. baumannii plasmid that harbors the blaOXA-58 and blaNDM-1 genes. The location of the blaOXA-58 and blaNDM-1 genes was confirmed through Southern blot hybridization assays. Antimicrobial susceptibility tests were conducted, and molecular characterization was performed using PCR and PFGE. MLST analysis revealed considerable genetic diversity among blaOXA-58 and blaNDM-1 positive strains in Brazil. It was confirmed that these genes were located on a plasmid larger than 300 kb in isolates from the same hospital, which also carry other antimicrobial resistance genes. Different genetic contexts were observed for the co-occurrence of these carbapenemase-encoding genes in Brazilian strains. The propagation of blaOXA-58 and blaNDM-1 genes on the same plasmid, which also carries other resistance determinants, could potentially lead to the emergence of bacterial strains resistant to multiple classes of antimicrobials. Therefore, the characterization of these strains is of paramount importance for monitoring resistance evolution, curbing their rapid global dissemination, averting outbreaks, and optimizing therapy.